Jerusalem commands - Moorcock, Michael 1939- (A Phoenix Paperback, 1992)
The third novel of the Pyat quartet finds Maxim Arturovitch Pyatnitski scheming his way from New York to Hollywood, Cairo to Marrakesh. He finds cult success as a star of the silver screen winning and breaking many hearts along the way, mixing with characters good and bad, real and unreal. But everything he does with panache as he makes his way to an appointment with the twentieth century's blackest moment. Book four of the Pyat quartet is in preparation.